1992
DOI: 10.1093/oxfordjournals.humrep.a137804
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and meiotic studies in an infertile man with Y; 13 translocation

Abstract: Clinical and meiotic studies were done on an infertile man with a translocation between Yq and 13q, who was identified through the birth of his son with partial trisomy 13q. Seminal plasma transferrin showed preserved Sertoli cell function while lactate dehydrogenase C4 indicated hypospermatogenesis. A quadrivalent in diakinesis and spermatogenic arrest in the second meiotic division was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This report demonstrate the unique importance of a single growth factor in the regulation of spermatogenesis in mice. Because abnormal spermatogenesis is a feature of many cases of infertility in human males (27,28), the mice generated in this study may be useful models to study infertility in human males.…”
Section: Discussionmentioning
confidence: 99%
“…This report demonstrate the unique importance of a single growth factor in the regulation of spermatogenesis in mice. Because abnormal spermatogenesis is a feature of many cases of infertility in human males (27,28), the mice generated in this study may be useful models to study infertility in human males.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have reported an azoospermic man with a reciprocal translocation t(Yq;13q) and his son with partial trisomy 13q resulting from a paternally inherited translocation (Nikolis et al 1991;Micic et al 1992).…”
Section: Discussionmentioning
confidence: 99%